THE DEVELOPMENT OF EDUCATIONAL GAME WITH SPINNING WHEELS FOR SPEAKING CLASS TO THE TENTH GRADE OF MADYATAMA VOCATIONAL HIGH SCHOOL PALEMBANG - Anggraini, Anggi; Jaya, Aswadi; Hermansyah (Universitas PGRI Palembang, 2024)
The objective of this research was to develop of educational game with spinning wheels for speaking class to the tenth grade of Madyatama Vocational High School Palembang. The method use in this development is the ADDIE (analysis, design, development, implementation, and evaluation) model. Data was collected through interviews, tests (one-to-one test and small group test), and questionnaires to assess the needs of students and teachers regarding speaking activities in the classroom. The research results show that the development of spinning wheels media for English speaking classes are declared valid with percentage score of 95,4%, the practicality value gets a percentage score of 95,3% with very practical criteria, and the effectiveness value gets a percentage score of 89,1% with a very effective category. It means that the development of educational game with spinning wheels for speaking class was very valid, and suitable to be implemented in speaking class.